2019
DOI: 10.1021/acs.joc.9b01835
|View full text |Cite
|
Sign up to set email alerts
|

Hunterines A–C, Three Unusual Monoterpenoid Indole Alkaloids from Hunteria zeylanica

Abstract: Three new monoterpenoid indole alkaloids (MIAs), hunterines A−C (1−3), were isolated from Hunteria zeylanica. Compound 1 possesses a unique skeleton with an unprecedented azabicyclo[4.3.1]decane ring system. Compounds 2 and 3 are a pair of epimeric vobasinylindole alkaloid heterodimers. Their structures including absolute configurations were established by spectroscopic analyses, X-ray diffraction, computational calculation, and the modified Mosher's method. Plausible biogenetic pathways of 1−3 were also propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Alashanine A ( 1 ) was tested for antibacterial effect against Bacillus subtilis and anti- Candida albicans by the established bioassay methods. , The results showed that 1 exhibited significant inhibition against Bacillus subtilis with a MIC value of 5.31 μg/mL. In addition, the cytotoxic activity of 1 against the growth of HepG2 and MCF-7 human cancer cell lines was tested by the MTT method. Alashanine A ( 1 ) was found to possess moderate cytotoxic activity in vitro . The IC 50 values of 1 against HepG2 and MCF-7 cells were 9.16 and 5.01 μM, respectively (taxol as the positive control, Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…Alashanine A ( 1 ) was tested for antibacterial effect against Bacillus subtilis and anti- Candida albicans by the established bioassay methods. , The results showed that 1 exhibited significant inhibition against Bacillus subtilis with a MIC value of 5.31 μg/mL. In addition, the cytotoxic activity of 1 against the growth of HepG2 and MCF-7 human cancer cell lines was tested by the MTT method. Alashanine A ( 1 ) was found to possess moderate cytotoxic activity in vitro . The IC 50 values of 1 against HepG2 and MCF-7 cells were 9.16 and 5.01 μM, respectively (taxol as the positive control, Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the first observation indicated the need for cautiousness in the interpretation of experimental data, the second observation provided hope that semi-synthetic transformations ( e.g. , Mosher ester formation) could be adequately controlled to create a series of differentially esterified products for analysis. …”
Section: Resultsmentioning
confidence: 99%
“…Colorless crystals of 1 and 2 were obtained from MeOH at room temperature. The X-ray crystallographic data were collected on a Super Nova (Dual, Cu at zero, AtlasS2) diffractometer with Cu Kα radiation (λ = 1.54184 Å) at 100.00 (10) K. After we used Olex2, the structures were solved with the ShelXT structure solution program using intrinsic phasing and refined with the ShelXL refinement package using least-squares minimization. Crystallographic data of compound 1 (CIF 1 and Table S1) and compound 2 (CIF 2 and Table S2) have been deposited at the Cambridge Crystallographic Data Center, and the deposition numbers of 1 and 2 were CCDC 1916494 and CCDC 1916493, respectively. Copies of the data can be obtained on application to the CDCC free of charge, 12 Union Road, Cambridge, CB21EZ, United Kingdom [Phone: + 44 (0) 1223 336408; Fax: + 44 (0) 1223 336033; Email: deposit@ccdc.ac.uk].…”
Section: Methodsmentioning
confidence: 99%